Abnormal fibre usage in UC in remission. Issue 4 (18th July 2014) - James, Sally L; Christophersen, Claus T; Bird, Anthony R; Conlon, Michael A; Rosella, Ourania; Gibson, Peter R; Muir, Jane G
Abstract : Objective: Colonic fermentation in patients with UC in remission was compared with that in matched healthy subjects on habitual diets and when dietary fibre was increased. Design: Fibre intake, faecal output of fibre (measured as non-starch polysaccharide (NSP)), starch, microbiota and fermentation products, and whole gut transit time (WGTT) were assessed in association with habitual diet and when dietary intake of wheat bran (WB)-associated fibre and high amylose-associated resistant starch (RS) was increased in an 8-week, randomised, single-blind, cross-over study. Results: Despite a tendency to lower habitual fibre intake in UC patients, faecal NSP and starch concentrations were threefold higher than in controls, whereas concentrations of phenols and short-chain fatty acids, pH and WGTT were similar. Increasing RS/WB intake was well tolerated. In controls (n=10), it more than doubled faecal NSP and starch excretion (p=0.002 for both), had no effect on NSP usage and reduced WGTT (p=0.024). In UC patients (n=19), high intake of RS/WB tended to normalise gut transit, but did not increase the proportion of NSP fermented. Increasing intake of RS/WB had little effect on faecal fermentation patterns or the structure of the microbiota. However, faeces from the UC cohort had lower proportions of Akkermansia muciniphila and increased diversity within Clostridium cluster XIVa compared to controls. Conclusions: Gut fermentation of NSP and starch is diminished in patients with UC. This cannot be explained by abnormal gut transit and was not corrected by increasing RS/WB intake, and may be due to abnormal functioning of the gut microbiota. Trial registration number: Australian New Zealand Clinical Trials Registry: ACTRN12614000271606.